PENGARUH KUALITAS PRODUK DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA PADMA HERBAL BALI DI KABUPATEN TABANAN - NI GUSTI AYU PUTRI NURYATI; I NYOMAN GEDE MARTA; I GUSTI AYU META PURMINA DEWI (Jurnal Ilmiah Satyagraha, 2023)
With the advancement of technology in various fields like today,the business world is increasingly competitive in business, especially inIndonesia which is marked by the existence of herbal companies that offermany quality herbal products and are able to compete in the market. Everycompany always tries to maintain the company's survival by makingeffective and quality products so that customers feel satisfied and remainloyal to the company. Padma Herbal is a herbal company that marketshealth products, because the quality of its products has been highly trustedby consumers from year to year, making this company grow rapidly.Seeing this background, this thesis is entitled: "The Influence of ProductQuality and Customer Satisfaction on Customer Loyalty at Padma HerbalBali in Tabanan Regency. The formulation of the problem is how doesproduct quality and customer satisfaction influence customer loyalty atPadma Herbal Bali in Tabanan Regency. The purpose of this research wasto find out and analyze the effect of product quality and customersatisfaction on customer loyalty at Padma Herbal Bali. Data collectionmethods are carried out by means of observation, interviews, andquestionnaires. The number of respondents in this study was 65, thedistribution of questionnaires was carried out using the accidental samplemethod. In the first hypothesis test (t test) H0 is rejected and H1 isaccepted, because the tcount is 4.752 > ttable 1.999 and the significancevalue is 0.000 <0.05. it can be concluded that variable X1 has a positiveand significant effect on variable Y. The second hypothesis test (t test) H0is rejected and H2 is accepted, because the tcount is 2.946 > ttable 1.999and the significance value is 0.005 <0.05. It was concluded that variableX2 had a positive and significant effect on variable Y. The third hypothesistest (Test F) H0 was rejected and H3 was accepted, because the Fcountvalue was 50.616 > Ftable 3.15 and a significance value of 0.000 <0.05. Itwas concluded that variables X1 and X2 had a positive and significanteffect on variable Y